THE ANTITHROMBOTIC EFFECT OF PALM OIL IS CORRELATED WITH ITS CONTENTS OF VITAMIN E - Hornstra, E G; Hennissen, A H; Kalafusz, R; Tan, D T S (Thrombosis and Haemostasis, 1987)
Dietary saturated fatty acids are known to increase platelet aggregation and arterial thrombogenesis.We recently demonstrated, however, that palm oil, rich in saturated palmitic acid, has a distinct antithrombotic affect, which is associated with a decrease of the thromboxane-prostacyclin ratio in activated whole blood. To identify the antithrombotic component(s) of palm oil, seven palm oil fractions were prepared with comparable fatty acid compositions of the triglycerides but containing Various amounts of non-triglyceride material with different compositions.These fractions were fed to rats in amounts of 50 energy% for a period of 8 weeks, after which arterial thrombosis tendency was measured upon insertion of an aortic prosthesis, the aorta-loop. During loop insertion, 1 ml blood was collected in citrate for measuring platelet aggregation and ATP release in response to collagen, using the Chronolog whole blood lumi-aggregometer. Arterial thrombosis tendency was found to be negatively related to the total amount of non-triglyceride material in the various fractions (r = 0.78; p <0.05).No significant relationship was observed between arterial thrombus formation and the various sterols present in the non-triglyceride material.A significant negative correlation was found, however, with a-tocopherol (r = 0.86; p <.02). Collagen-induced platelet aggregation and ATP release in whole blood were not correlated to total amounts or α-tocopherol content of the non-triglyceride material.However, significant positive relationships were found between these platelet functions and the amountsof the various sterols (Campesterol: r = 0.70; P < 0.10 β-sitostero1 : r = 0.69; P <0.10. Cholesterol : r = 0.81; P < 0.05).These findings demonstrate that effects of edible oils on platelet function and arterial thrombogenesisare not only mediated by the fatty acid compostion of the triglycerides, but can also be determined by 'minor components', present in the non-triglyceride part of the oils.